Engaging underrepresented patient groups in specialised treatment: qualitative results from the PROVIDE-C randomised trial on integrated mental health video consultations for depression and anxiety - Müller, Selina; Ritter-von Kramer, Alexa; Tönnies, Justus; Wildenauer, Alina; Wensing, Michel; Friederich, Hans-Christoph; Haun, Markus W. (BMC public health, 2025)
Mental health specialist video consultations (MHSVC) offer a promising way to address the growing burden of depression and anxiety. However, their acceptance among groups with lower mental health care uptake and limited technology literacy remains underexamined.
Gesehen am 12.02.2026